INTERPRETATION OF SOCIALITY IN PHILOSOPHICAL TRADITION - Лукашенко, М. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The specificity and phase development of sociality as mirrored in philosophical studies have been examined in the article. Basic paradigms of sociality and their logical grounds of formation in context of their cultural, historical and spiritual preconditions of different epochs are substantiated. A systemic approach to the formation of sociality through the change of metaphysical, classical, non-classical and postclassical stages of its structuring is considered.